2008
DOI: 10.1111/j.1470-6431.2008.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of foods and foodstuffs processed with hazardous chemicals: a case study of Bangladesh

Abstract: Determining the best way to persuade consumers to consume more healthy foods is challenging. In Bangladesh, however, daily newspapers consistently show that various hazardous chemicals (e.g. calcium carbide, sodium cyclamate, cyanide and formalin, etc.) are mixed with or added to foods and foodstuffs. These chemicals are very dangerous to humans. This present study examines the reasons behind the use of hazardous chemicals in foods as well as the extent to which food producers/sellers use such chemicals. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…The consumer preference for dried fish products is not only because of their traditionally desirable taste and flavor, but also their high content of omega-3 polyunsaturated fatty acids especially in fish lipids, which have various health benefits for human [5]. Now-adays, people are more concern about health and nutritional issues [6][7][8][9][10][11][12] and they also concern about the nutritional value of food items when they buy them for their household. Biochemical analysis provides information on the nutritional value of a particular organism used as a source of food [13].…”
Section: Introductionmentioning
confidence: 99%
“…The consumer preference for dried fish products is not only because of their traditionally desirable taste and flavor, but also their high content of omega-3 polyunsaturated fatty acids especially in fish lipids, which have various health benefits for human [5]. Now-adays, people are more concern about health and nutritional issues [6][7][8][9][10][11][12] and they also concern about the nutritional value of food items when they buy them for their household. Biochemical analysis provides information on the nutritional value of a particular organism used as a source of food [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Calcium carbide, which is otherwise used in making fertilisers, in steelmaking, and to produce acetylene gas, is carcinogenic in its effect and very harmful to human health (Per et al 2007;Hossain et al 2008). Per et al (2007) warn that Calcium carbide should not be used for fruit and vegetable ripening because traces of the chemical can be fatal if consumed.…”
Section: Consumers' Concernsmentioning
confidence: 99%
“…25 However, these types of food safety controls are not commonly implemented in Bangladesh because of an insufficient number of qualified inspectors, their lack of motivation to visit remote fish-processing plants, and corruption at different levels. 25,32 Therefore, persons are at increased risk of pufferfish poisoning because of the limited capacity of government authorities to ensure safe handling of toxic fish.…”
Section: Discussionmentioning
confidence: 99%